Подождите немного. Документ загружается.
I
1
= I
2
~
K = 0 Ω
z
= const
˙
Ω
x
− ωΩ
y
= 0,
˙
Ω
y
+ ωΩ
x
= 0, ω =
I
1
− I
3
I
1
Ω
z
.
Ω
x
= a sin(ωt + α), Ω
y
= a cos(ωt + α),
a α
~
Ω xoy
ω
OZ
oz M
z
= I
3
Ω
z
M
z
= M cos θ θ oz
OZ
˙
θ
˙ϕ =
r
Ω
2
x
+ Ω
2
y
sin θ
=
r
M
2
x
+ M
2
y
I
1
sin θ
=
M
I
1
.
˙ϕ
Ω
z
Ω
z
=
M
z
I
3
=
M cos θ
I
3
.
ψ =
π
2
−
π
4
t, θ =
π
3
, ϕ = πt.
0, 0, 32
2a M
m xyz
x
0
y
0
z
0
oz oz
0
m
a b
m R H
m a b c
R m
α
r m
R
r/R
r
R
l m
OA Ω
O AB Ox
q
i
s
p
i
=
∂L
∂ ˙q
i
.
q
i
, ˙q
i
t
dL =
X
i
(
∂L
∂
˙
q
i
d ˙q
i
+
∂L
∂q
i
dq
i
) +
∂L
∂t
dt =
X
i
(p
i
d ˙q
i
+
∂L
∂q
i
dq
i
) +
∂L
∂t
dt.
p
i
d ˙q
i
= d(p
i
˙q
i
) − ˙q
i
dp
i
,
d(L −
X
i
p
i
˙q
i
) =
X
i
(−˙q
i
dp
i
+
∂L
∂q
i
dq
i
) +
∂L
∂t
dt.
q
i
p
i
t
H
H = H(q
i
, p
i
, t) =
X
i
p
i
˙q
i
− L.
H
q
i
p
i
t
˙q
i
=
∂H
∂p
i
,
∂L
∂q
i
= −
∂H
∂q
i
,
∂L
∂t
= −
∂H
∂t
.
˙q
i
p
i
˙q
i
=
∂H
∂p
i
, ˙p
i
= −
∂H
∂q
i
.
q
i
p
i
2s
S =
Z
t
2
t
1
X
i
p
i
dq
i
− H dt.
δS =
Z
t
2
t
1
X
i
(δp
i
dq
i
+ p
i
δ(dq
i
) − (
∂H
∂q
i
δq
i
+
∂H
∂p
i
δp
i
) dt).
δS =
Z
t
2
t
1
X
i
(δp
i
(dq
i
−
∂H
∂p
i
dt) − δq
i
(dp
i
+
∂H
∂q
i
dt)).
δq
i
δp
i
dq
i
−
∂H
∂p
i
dt = 0, dp
i
+
∂H
∂q
i
dt = 0.
dt
L =
1
2
m( ˙r
2
+ r
2
˙ϕ
2
) − U(r, ϕ),
p
r
=
∂L
∂ ˙r
= m ˙r, p
ϕ
=
∂L
∂ ˙ϕ
= mr
2
˙ϕ.